Best Practices and Recommendations for Digital Interventions to Improve Engagement and Adherence in Chronic Illness Sufferers - Karekla, Maria; Kasinopoulos, Orestis; Dias Neto, David; Ebert, David; Van Daele, Tom; Nordgreen, Tine; Hoefer, Stefan; Oeverland, Svein; Jensen, Kit Lisbeth (European Psychologist, 2019)
Chronic illnesses cause considerable burden in quality of life, often leading to physical, psychological, and social dysfunctioning of the sufferers and their family. There is a growing need for flexible provision of home-based psychological services to increase reach even for traditionally underserved chronic illness sufferer populations. Digital interventions can fulfill this rote and provide a range of psychological services to improve functioning. Despite the potential of digital interventions, concerns remain regarding users' engagement, as low engagement is associated with low adherence rates, high attrition, and suboptimal exposure to the intervention. Human-computer interaction (e.g., theoretical models of persuasive system design, gamification, tailoring, and supportive accountability) and user characteristics (e.g., gender, age, computer literacy) are the main identified culprits contributing to engagement and adherence difficulties. To date, there have not been any clear and concise recommendations for improved utilization and engagement in digital interventions. This paper provides an overview of user engagement factors and proposes research informed recommendations for engagement and adherence planning in digital intervention development. The recommendations were derived from the literature and consensualized by expert members of the European Federation of Psychology Associations, Psychology and Health Standing Committee, and e-Health Task Force. These recommendations serve as a starting point for researchers and clinicians interested in the digitalized health field and promote effective planning for engagement when developing digital interventions with the potential to maximize adherence and optimal exposure in the treatment of chronic health conditions.
CRIS-Team WoS Importer:2019-05-21